Reconstitution and optimisation of the biosynthesis of bacterial sugar pseudaminic acid (Pse5Ac7Ac) enables preparative enzymatic synthesis of CMP-Pse5Ac7Ac - Harriet S. Chidwick; Emily K. P. Flack; Tessa Keenan; Julia Walton; Gavin H. Thomas; Martin A. Fascione (Scientific Reports, 2021)
Abstract Pseudaminic acids present on the surface of pathogenic bacteria, including gut pathogens Campylobacter jejuni and Helicobacter pylori, are postulated to play influential roles in the etiology of associated infectious diseases through modulating flagella assembly and recognition of bacteria by the human immune system. Yet they are underexplored compared to other areas of glycoscience, in particular enzymes responsible for the glycosyltransfer of these sugars in bacteria are still to be unambiguously characterised. This can be largely attributed to a lack of access to nucleotide-activated pseudaminic acid glycosyl donors, such as CMP-Pse5Ac7Ac. Herein we reconstitute the biosynthesis of Pse5Ac7Ac in vitro using enzymes from C. jejuni (PseBCHGI) in the process optimising coupled turnover with PseBC using deuterium wash in experiments, and establishing a method for co-factor regeneration in PseH tunover. Furthermore we establish conditions for purification of a soluble CMP-Pse5Ac7Ac synthetase enzyme PseF from Aeromonas caviae and utilise it in combination with the C. jejuni enzymes to achieve practical preparative synthesis of CMP-Pse5Ac7Ac in vitro, facilitating future biological studies.